2018
DOI: 10.1038/s41391-018-0083-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the contribution of demographics, access to health care, treatment, and tumor characteristics to racial differences in survival of advanced prostate cancer

Abstract: Our analysis of men with advanced PCa revealed worse OS among Blacks. However, when access to care, treatment, and cancer characteristics are accounted for, Black race was associated with better OS. These findings suggest that initiatives to improve access to care may represent an effective tool to reduce disparities in PCa outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…Patients with T3 or T4 stage are also known as locally advanced prostate cancer. Krimphove et al reported that PCa with T3 or T4 had a worse overall survival [27]. Meanwhile, the Gleason score is the sum of the two most common grade patterns in PCa, which act as the single most potent predictor of PCa outcomes [28].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T3 or T4 stage are also known as locally advanced prostate cancer. Krimphove et al reported that PCa with T3 or T4 had a worse overall survival [27]. Meanwhile, the Gleason score is the sum of the two most common grade patterns in PCa, which act as the single most potent predictor of PCa outcomes [28].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in that analysis, black race was associated with better overall survival. 3 Data from several clinical trials point in the same direction. George et al 16 reported that black men had better a progression-free survival rate compared with white men (16.6 months vs 11.5 months) when treated with abiraterone and prednisone.…”
Section: Discussionmentioning
confidence: 93%
“…2,4 Additionally, we found that when patient and sociodemographic factors are taken into account, the differences were actually reversed, that is, black men may have had better survival than white men. 3 Taken together, these findings may provide more evidence of a racial disparity, suggesting a form of social injustice rather than racial difference attributable to biology.…”
Section: Introductionmentioning
confidence: 88%
“…In more recent literature, the impact of genomic differences by race has been found to be relatively small and limited to patients with lower Gleason scores (3). The vast majority of racial disparity between black and nonblack patients appears to be driven by socioeconomic factors such as access to care (4), and racial differences in prostate cancerespecific mortality which is most pronounced among men with Gleason 6 disease (5). Furthermore, racial disparities persist in the utilization of brachytherapy which is an effective and commonly used treatment modality for men with low-risk disease (6).…”
Section: Introductionmentioning
confidence: 99%